Designating Prisoners as Justice Collaborators in the Pursuit of Justice - Fariz Dyza Suryanegara; Erny Herlin Setyorini (Mimbar Keadilan, 2025)
This research studies is the authority of the prosecutor's office in determining prisoners as justice collaborators. This research is research with a normative juridical type, statutory approach, conceptual and comparative approach, as well as deductive legal material analysis techniques to analyze the types and sources of primary and secondary legal materials. The aim of this research is to analyze the urgency of the Republic of Indonesia Prosecutor's authority in determining justice collaborator status for prisoners and its concept. The research results reveals that this concept of regulating the authority of the Republic of Indonesia Prosecutor's Office in determining justice collaborator status for convicts is in the form of a concept. First, the concept of regulating the designation of prisoners as justice collaborators based on Law No. 8 of 1981 concerning Criminal Procedure Law. Second, the designation of convicts as justice collaborators with a benefit orientation as a legal goal. Third, the concept of determining prisoners as justice collaborators is oriented towards justice as a legal goal. From these several concepts, the author urges the immediate formulation of legislative regulations in Indonesia to fill the legal vacuum in determining prisoners as justice collaborators, especially the Indonesian Attorney General's Office and the Indonesian DPR to make changes (revisions) to Law No. 31 of 2014 concerning Amendments to Law No. 13 of 2006 concerning Witness and Victim Protection. Also, the DPR RI also changed Law No. 11 of 2021 concerning Amendments to Law No. 16 of 2004 concerning the Indonesian Attorney General's Office by increasing the authority of the Prosecutor in determining justice collaborators for prisoners in this law.